2023
DOI: 10.1007/s12633-023-02525-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Preparation and Properties of Porous Silicon Nitride Ceramics

Hong-kai Zha,
Wen-qing Yu,
Jing-wei Li
et al.

Abstract: Porous silicon nitride ceramics is a promising functional ceramic material. In recent years, the research on the preparation of porous silicon nitride ceramics within different methods has been widely investigated. First, this work reviews the main synthesis methods of Si 3 N 4 porous ceramics in detail, and compares the differences between strength and porosity caused by each method. The characteristics and advantages of different technologies under the current co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Taking these into consideration, some new ceramic preparation methods were developed accordingly. 105 Polymer-derived ceramics (PDCs) technology is one of the most important preparation methods. Compared with other preparation processes, the required sintering temperature of PDCs route is lower, and no auxiliary materials is required.…”
Section: Dielectric Loss Mamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking these into consideration, some new ceramic preparation methods were developed accordingly. 105 Polymer-derived ceramics (PDCs) technology is one of the most important preparation methods. Compared with other preparation processes, the required sintering temperature of PDCs route is lower, and no auxiliary materials is required.…”
Section: Dielectric Loss Mamsmentioning
confidence: 99%
“…Due to the high sintering temperature and the long sintering time, ceramic MAMs have the problems of high preparation cost and complicated process. Taking these into consideration, some new ceramic preparation methods were developed accordingly . Polymer-derived ceramics (PDCs) technology is one of the most important preparation methods.…”
Section: Research Progresses Of Mamsmentioning
confidence: 99%
“…15 Porous inorganic nonmetallic materials, such as ceramic foams, eliminate the shortcomings of organic and metallic materials and demonstrate unique advantages, such as good thermal and chemical stability, which make them ideal candidates for sound reduction in crucial environments. 16–18 For example, Du et al investigated the effect of structural factors on the sound absorption properties of silicon nitride ceramic foams and the results revealed that higher porosity and smaller pore size were conducive to better sound absorption by these ceramic foams. 7 They could withstand a sintering temperature of 1700 °C, indicating that such ceramic foams could be used in critically high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…12 Composites with low dielectric constant can be prepared by introducing the second phase with a low dielectric constant and high strength and combining the pores with the second phase of low dielectric constant. [13][14][15][16] Boron nitride (BN) possesses a low dielectric constant and unique lamellar structure, which can introduce certain pores when the lamellar grains overlap. Feng et al 17 introduced BN to reduce the dielectric constant of silicon nitride ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that mechanical properties become worse with increased porosity 12 . Composites with low dielectric constant can be prepared by introducing the second phase with a low dielectric constant and high strength and combining the pores with the second phase of low dielectric constant 13–16 . Boron nitride (BN) possesses a low dielectric constant and unique lamellar structure, which can introduce certain pores when the lamellar grains overlap.…”
Section: Introductionmentioning
confidence: 99%